An Integrated Transcriptomics and Lipidomics Analysis Reveals That Ergosterol Is Required for Host Defense Against Bacterial Infection in Drosophila - Deng, Zihao; Yang, Yanyang; Luo, Jiazhen; Zhang, Biling; Liu, Jiyong; Shui, Guanghou; Jiao, Renjie; Wei, Chuanxian (Frontiers in Immunology, 2022)
Animals adjust their lipid metabolism states in response to pathogens infection. However, the underlying molecular mechanisms for how lipid metabolism responds to infection remain to be elusive. In this study, we assessed the temporal changes of lipid metabolism profiles during infection by an integrated transcriptomics and lipidomics analysis. Ergosterol is identified to be required for proper host defense to pathogens. Notably, ergosterol level is increased in the hemolymph upon bacterial infection. We show that the increase of ergosterol level by food supplement or genetic depletion of Acsl, a long-chain fatty acid-CoA synthetase, promotes host survival against bacterial challenges. Together, our results suggest a critical role of lipid metabolism adaption in the process of host defense against invading pathogens.